Exploring the Efficacy of Matra Basti in Managing Janusndhigata Vata - Ramya S; Anita Choudarya; Ananta.S.Desai; Shakunttala S P (AYUSHDHARA, 2025)
Sandhigata vata is the most common articular disorder. It is a type of Vatavyadhi which mainly occurs in old age due to Dhatukshaya. Sandhigata vata mainly presents with Sandhi shoola and Shopha further leading to difficulty in movements. If these Lakshanas are observed in the Janu Sthana, the condition is referred to as Janusandhigata Vata, which can be correlated with osteoarthritis. The prevalence of osteoarthritis among the elderly, as per a recent study, is 56.6%. The present case study involves a 60-year-old female patient presenting with a two-year history of pain and swelling in both knee joints, along with an inability to walk independently without walker over the past 15 days. The condition was diagnosed as Janusandhigata Vata (osteoarthritis of the knee joints). For its management, Godhumadi upanaha, Sarvananga abhyanga with Ksheerabala taila followed by Shashtikashali pinda sweda followed by 21 days Matra basti with Ksheerabala taila and Guggulu tiktaka grita and Shamana chikithsa were administered. Following the procedure, the patient experienced significant relief in both subjective and objective parameters like X-ray.